2021
DOI: 10.1016/j.heliyon.2021.e06651
|View full text |Cite
|
Sign up to set email alerts
|

The sources and quality of Iranian honey

Abstract: Iran is one of the largest honey-producing countries worldwide and is considered as an important source of honey for international markets. However, since Iran is not registered for honey export to Europe, the quality of Iranian honey remains unknown to European traders. As the first step in filling this gap, we analyzed 225 honey samples using palynology, sensory, nuclear magnetic resonance (NMR) and conventional physicochemical analyses as outlined by the European Union coordinated control plan. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The analytical methods, the sensory evaluation of honey can complement the confirmation of the botanical origin, establish sensory profiles for monofloral honey, verify quality, among others [ 118 ], since various studies have observed differences in the characteristics of honeys according to their floral and geographical origin [ 50 , 60 , 119 , 120 , 121 ]…”
Section: The Color Of the Honey And Phenolic Compoundsmentioning
confidence: 99%
“…The analytical methods, the sensory evaluation of honey can complement the confirmation of the botanical origin, establish sensory profiles for monofloral honey, verify quality, among others [ 118 ], since various studies have observed differences in the characteristics of honeys according to their floral and geographical origin [ 50 , 60 , 119 , 120 , 121 ]…”
Section: The Color Of the Honey And Phenolic Compoundsmentioning
confidence: 99%
“…Iran is one of the most important honey-producing countries worldwide. According to the data released by the Food and Agriculture Organization of the United Nations (FAOSTAT), Iran was among the 10 largest honey-producing countries during 1993-2018 (FAOSTAT, 2018) [ 8 ]. However, several researchers have investigated the quality of Iranian honey, concluding a lack of compliance with the international standards [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the data released by the Food and Agriculture Organization of the United Nations (FAOSTAT), Iran was among the 10 largest honey-producing countries during 1993-2018 (FAOSTAT, 2018) [ 8 ]. However, several researchers have investigated the quality of Iranian honey, concluding a lack of compliance with the international standards [ 8 , 9 ]. The reason is the lack of a periodical and accurate monitoring program authenticated by authorized legislations.…”
Section: Introductionmentioning
confidence: 99%
“…Iran is the world's thirdlargest producer of honey and has the resources to produce quality monofloral honey. However, in the study [17], signs of adulterated honey were found in 85% of the samples. A massive method of fraud in the country is feeding of bees with sugar during the feeding season.…”
Section: Fig 2 Honey Production In Russia (Data By Farm Categories Tons)mentioning
confidence: 66%